(untitled) (Journal of Economic Research & Business Administration, 2015)
In the world literature there is no common understanding of the concept of corporate social responsibility (CSR). The article explains the relevance of the concept CSR for Kazakhstani companies. Issues of corporate social responsibility for sustainable development should be based on national priorities and features, as well as the active participation of companies in the relevant international processes, programs and initiatives. Contemporary companies themselves must determine the measure of participation in social programs, depending on their state of business. On the other hand the introduction of international standards of corporate social responsibility will ensure the further modernization of society. An article highlights the following understanding of Social Corporate Responsibility (SCR), which is the contribution of business representatives in the development of society in the social, economic and environmental spheres, on a voluntary basis. This contribution may be associated with both the company’s core business, and going beyond its frames .